2005
DOI: 10.1172/jci23196
|View full text |Cite
|
Sign up to set email alerts
|

Induction of prolonged survival of CD4+ T lymphocytes by intermittent IL-2 therapy in HIV-infected patients

Abstract: HIV infection leads to decreases in the number of CD4 + T lymphocytes and an increased risk for opportunistic infections and neoplasms. The administration of intermittent cycles of IL-2 to HIV-infected patients can lead to profound increases (often greater than 100%) in CD4 cell number and percentage. Using in vivo labeling with 2 H-glucose and BrdU, we have been able to demonstrate that, although therapy with IL-2 leads to high levels of proliferation of CD4 as well as CD8 lymphocytes, it is a remarkable pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 25 publications
(30 reference statements)
4
101
0
Order By: Relevance
“…Although isotope labeling studies in humans are typically restricted to blood, it has been reported that labeling kinetics in human T cells derived from blood and lymphoid tissues are comparable (29). Label incorporation in T cells derived from mouse peripheral lymph nodes and spleen was also similar (unpublished data).…”
Section: Discussionmentioning
confidence: 86%
“…Although isotope labeling studies in humans are typically restricted to blood, it has been reported that labeling kinetics in human T cells derived from blood and lymphoid tissues are comparable (29). Label incorporation in T cells derived from mouse peripheral lymph nodes and spleen was also similar (unpublished data).…”
Section: Discussionmentioning
confidence: 86%
“…IL-2 and IL-7 administered to HIV-1-infected individuals was shown to enhance the frequency of CD4 + T cells (29,(54)(55)(56). In SIV-infected macaques, IL-15 failed to improve viral loads after a therapeutic SIV vaccine, and it had no effect on SIV-specific CD8 + function (57).…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, a large set of clinical trials demonstrated that intermittent interleukin (IL)-2 therapy increased the CD4 T cell pool in HIV-infected patients and induced, in a large majority of patients, significant and sustained increases in CD4 T cell count beyond that seen in patients treated with antiviral drugs alone. In particular, recombinant IL-2 therapy raised naive and central memory CD4 + cells expressing CD25, the α-chain of the IL-2 receptor, more than antiretroviral drugs alone (1)(2)(3)(4)(5)(6). This population accounted for up to 70% of the total CD4 + T cell pool of IL-2-treated patients and persisted for a long time.…”
mentioning
confidence: 99%